2017
DOI: 10.5455/ajvs.258621
|View full text |Cite
|
Sign up to set email alerts
|

Some Haematological and Serum Biochemical Parameters in Apparently Clinically Healthy Hassawi Donkey

Abstract: Key words: Donkey, Hassawi, blood, haematology, serumThe Hassawi donkey breed represents one of the most common native donkey breeds in the Middle East taking its name from the Al-Hasa region in the Eastern province of Saudi Arabia. Due to the lack of information about the main haematological and serum biochemical parameters of Hassawi donkey breed, this study aimed at the determination of reference base-line values regarding haematological and biochemical parameters. Four physiological, sixteen haematological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…According to the present results, most biochemical parameters in Shetland ponies were lower than that reported for Arabian horses except TP, which was more in Shetland ponies [21] . However, when comparing the present results with values reported in Hassawi donkey from the same area, it found higher values of GLOB, BUN, CK, TBIL and GLU and lower GGT and ALB in Shetland ponies than that reported in Hassawi donkey [4] . Differences in biochemical parameters values among previous studies could be explained by many factors like life condition, muscle mass, type of feeding and type of exercise.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…According to the present results, most biochemical parameters in Shetland ponies were lower than that reported for Arabian horses except TP, which was more in Shetland ponies [21] . However, when comparing the present results with values reported in Hassawi donkey from the same area, it found higher values of GLOB, BUN, CK, TBIL and GLU and lower GGT and ALB in Shetland ponies than that reported in Hassawi donkey [4] . Differences in biochemical parameters values among previous studies could be explained by many factors like life condition, muscle mass, type of feeding and type of exercise.…”
Section: Discussioncontrasting
confidence: 49%
“…However, with the exception of platelets, Shetland ponies have lower values of WBC, Lymphocyte, RBC and HGB in comparison to horses [21] . In addition, comparison of our results with values of haematological parameters of Hassawi donkeys that live in the same geographical area [4] showed that Shetland ponies have lower values in most haematological parameters like WBC, RBC, Lymphocyte, HBG, MCV, MCH, MCHC and MPV. Such differences observed between our results and results from previous studies may be due to differences in group size, geographical locations and assay methodology.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Despite the lack of specific knowledge on the risk factors for Se and Vit E deficiency or overdose in donkeys, authors such as Shawaf [28] and Bazzano et al [6] have reported interspecies and sex differences. Other authors have addressed additional factors such as the low levels of Se in the soil of certain regions to be sufficient to predispose newborn foals to develop pathological conditions, along with the possibility of donkeys having a lower Se blood profile when compared to horses [6].…”
Section: Introductionmentioning
confidence: 99%